2021
DOI: 10.1111/aos.14887
|View full text |Cite
|
Sign up to set email alerts
|

Development of angle closure and associated risk factors: The Handan eye study

Abstract: Purpose To investigate the development of angle closure from baseline open angle and associated risk factors in a rural Chinese population through a longitudinal study over a 5‐year period. Methods Subjects aged ≥30 years and older with bilateral open angles at baseline of the Handan Eye Study who participated in the follow‐up and had undergone both baseline and follow‐up gonioscopic examinations were included. Subjects with any form of angle closure, glaucoma, incisional ocular surgery or other conditions tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
2
13
0
1
Order By: Relevance
“…Females have shallow ACD as compared to males in the eastern population putting them at higher risks of acute attack of angle-closure and PACG. In the Handan Eye study, 6,830 eligible subjects aged 30 years or older with open-angle were recruited and undergone gonioscopic examinations at baseline and follow-up visits; the results showed that shallow central ACD was a significant risk factor for development of any form of angle closure after 5-year follow up ( OR = 0.110, P = 0.003) ( 5 ). In our study, ACD was significantly different among different myopia groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Females have shallow ACD as compared to males in the eastern population putting them at higher risks of acute attack of angle-closure and PACG. In the Handan Eye study, 6,830 eligible subjects aged 30 years or older with open-angle were recruited and undergone gonioscopic examinations at baseline and follow-up visits; the results showed that shallow central ACD was a significant risk factor for development of any form of angle closure after 5-year follow up ( OR = 0.110, P = 0.003) ( 5 ). In our study, ACD was significantly different among different myopia groups.…”
Section: Discussionmentioning
confidence: 99%
“…Implantation of an incorrect size ICL may lead to complications after the surgery, such as corneal endothelial damage, uveitis, and glaucoma ( 4 ). Besides, shallow central ACD was found to be an independent predictive risk factor for the development of any form of angle closure in the Handan Eye study ( 5 ) and in the Namil Study ( 6 ). Thus, it is important to identify such patients so that prophylactical treatment can be used to prevent an acute attack of angle-closure and primary angle-closure glaucoma (PACG).…”
Section: Introductionmentioning
confidence: 95%
“…The development of people‐centred health systems and the incorporation of modern technology for screening, if well connected to treatment and rehabilitation services, could reduce the number of undiagnosed glaucoma and alleviate the burden of the disease 112 84 and PACG (Asian descendants, hyperopia, female sex, and aged 40 years or older) 106–108 …”
Section: Discussionmentioning
confidence: 99%
“…There is a conspicuous body of information regarding specific risk factors for PACG. In summary, female sex, hyperopia, Asian descendants, age, and anterior chamber parameters have been repeatedly associated with the diagnosis of PACG 106–108 …”
Section: Risk Factors For Glaucoma Developmentmentioning
confidence: 95%
See 1 more Smart Citation